Identification, Efficacy, and Stability Evaluation of Succinimide Modification With a High Abundance in the Framework Region of Golimumab - Liu, Tao; Xu, Jin; Guo, Qingcheng; Zhang, Dapeng; Li, Jun; Qian, Weizhu; Guo, Huaizu; Zhou, Xinli; Hou, Sheng (Frontiers in Chemistry, 2022)
Succinimide (Asu) is the intermediate for asparagine deamidation in therapeutic proteins and it can be readily hydrolyzed to form aspartate and iso-aspartate residues. Moreover, Asu plays an important role in the protein degradation pathways, asparagine deamidation and aspartic acid isomerization. Here, an Asu modification with a high abundance in the framework region (FR) of golimumab was firstly reported, the effect of denaturing buffer pH on the Asu modification homeostasis was studied, and the results revealed that it was relatively stable over a pH range of 6.0–7.0, whereas a rapid decrease at pH 8.0. Then, the peptide-based multi-attribute method (MAM) analyses showed that the Asu formation was at Asn 43 in the FR of the heavy chain. Meanwhile, the efficacy (affinity, binding and bioactivity, complement-dependent cytotoxicity (CDC) and antibody-dependent cell-mediated cytotoxicity (ADCC) activity) and stability of the Asu modification of golimumab were evaluated, and the current results demonstrated comparable efficacy and stability between the Asu low and high abundance groups. Our findings provide valuable insight into Asu modification and its effect on efficacy and stability, this study also demonstrates that there is a need to develop a broad-spectrum, rapid, and accurate platform to identify and characterize new peaks in the development of therapeutic proteins, particularly for antibody drugs.